2019
DOI: 10.1093/nar/gkz1162
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyrimidinase protects from DNA replication stress caused by cytotoxic metabolites

Abstract: Imbalance in the level of the pyrimidine degradation products dihydrouracil and dihydrothymine is associated with cellular transformation and cancer progression. Dihydropyrimidines are degraded by dihydropyrimidinase (DHP), a zinc metalloenzyme that is upregulated in solid tumors but not in the corresponding normal tissues. How dihydropyrimidine metabolites affect cellular phenotypes remains elusive. Here we show that the accumulation of dihydropyrimidines induces the formation of DNA–protein crosslinks (DPCs)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 86 publications
1
15
0
Order By: Relevance
“…Moreover, since deficiency in enzymes downstream of DPD, such as dihydropyrimidase (DHP) and/or β-ureidopropionase (UDP), could alter the 5,6-Dihydrouracil catabolic pathway [57], our finding supports the possibility that DPD function could indicate an error of 5,6-Dihydrouracil metabolism detected in metabolomic analysis in our female ischemic stroke patients [54]. This possibility is supported by other studies [58,59] that DPD function could indicate an error of 5,6-Dihydrouracil metabolism.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, since deficiency in enzymes downstream of DPD, such as dihydropyrimidase (DHP) and/or β-ureidopropionase (UDP), could alter the 5,6-Dihydrouracil catabolic pathway [57], our finding supports the possibility that DPD function could indicate an error of 5,6-Dihydrouracil metabolism detected in metabolomic analysis in our female ischemic stroke patients [54]. This possibility is supported by other studies [58,59] that DPD function could indicate an error of 5,6-Dihydrouracil metabolism.…”
Section: Discussionsupporting
confidence: 89%
“…The increasing evidence also suggests that carcinogenesis was associated with metabolic reprogramming of the pyrimidine degradation pathway. Dihydrothymine, a decomposition product of thymine, was also considered as a potential cytotoxic metabolite and was up-regulated in both early lung adenocarcinoma and breast cancer (Basbous et al, 2020;Wikoff et al, 2015;Shaul et al, 2014), but in this study, it was found to be downregulated in the chemotherapyresistant group, which may be associated with enhanced activity of the degradation enzyme dihydropyrimidase (DHP).…”
Section: Discussionmentioning
confidence: 66%
“…Among the 9 risk genes, the relationship between DPYS and the development of HCC has not been reported. DPYS can affect the levels of dihydrouracil and dihydrothymine by regulating the metabolism of dihydropyrimidine, which is related to cell transformation and cancer progression [36]. Furthermore, we plotted the receiver operator characteristic curves (ROC) and calculated the AUC value to evaluate the sensitivity and speci city of the prognostic model (Fig.…”
Section: Discussionmentioning
confidence: 99%